The Rise of a New Type of Surveillance for Which the Law Wasn’t Ready - Levashov, Kirill (Science and Technology Law Review, 2013)
This article discusses the rising use of facial recognition technology in society and in law enforcement, and its legal implications. Section I describes the technology and how it works. While the potential uses for this technology are too numerous to list, this section goes on to describe the most widespread and troubling current uses, as well as some of the planned uses that illustrate the scope that the technology has the potential to achieve, and why that could be a problem. Section II discusses some of the more prevalent legal concerns that accompany the rise of this technology, such as privacy violations, chilling of free speech, and stalking. Section III analyzes the existing state of the law, and suggests some channels that may offer protection from the concerns raised in section II, while noting that these channels were not designed with facial recognition technology in mind so the protections offered may be weakened or, depending on the leanings of a court of law, nonexistent. The article closes by suggesting additional statutory protections that could be enacted to more completely address the issue, either piecemeal or as part of a larger regulatory scheme.